PENGARUH STRES KERJA, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA KANTOR PT. PLN (PERSERO) CILACAP JAWA TENGAH - Irna Sari Pratiwi; Hermin Endratno (Media Ekonomi, 2015)
This research was aimed at examining the impact of job stress, communication and work environment on employee job satisfaction in PT. PLN (Persero) Cilacap Jawa Tengah. The object of this research was the employees of PT. PLN (Persero) Cilacap Jawa Tengah, namely: PLN APJ Cilacap, UPJ Sidareja and UPJ Majenang. The total number was 85 persons (census). This research applied multiple regression analysis, T test and T test. The study results revealed that job stress was negatively related to employee satisfaction, while communication and work environment positively affected employee job satisfaction in PT. PLN (Persero) Cilacap Jawa Tengah. Keywords: Job Stress, Communication, Work Environment, Job Satisfaction